The Role of Stock Market Development in Influencing the Firms Performance: A Study Based on Pakistan Stock Market - Sophee Sulong, Bin Balia; Qasim, Saleem; Zeeshan, Ahmed (Canadian Center of Science and Education, 2018)
The study aims to examine the role of stock market development in influencing the performance of non financial firms listed on Pakistan Stock Exchange from 2001 to 2017. Stock market development is a foremost issue of debate nowadays in emerging and developing economies. The theories and empirical studies strongly refer that stock market development is a tool to mobilize the savings and investment to promote the industrialization and firms performance. This study is an effort to establish the empirical relationship between stock market development and firm‟s performance. Three indicators of stock market development like stock market volatility,stock market liquidity and stock market liquidity are used for assessing the book and market performance of firms. For this purpose two-step system Generalized Method of Moments (GMM) estimator was employed in a dynamic panel model for empirical testing of hypothesis. The findings indicates that stock market volatility is a significant factor which which attempts to decrease the firm performance. On the other hand, stock market capitalization and stock market liquidity significantly causes the increase in firm firm performance.